An Antarctic Waste Land: Apsley Cherry-Garrard, Cape Crozier and Emperor Penguins - N. Brazzelli (2016)
The youngest member of Scott’s last expedition, Apsley Cherry-Garrard did not take part in Scott’s final rush to the South Pole, but from June to August 1911, during the Polar night, with two companions, he set off on the “worst journey in the world” – a search for the never-before-seen breeding grounds of the Emperor Penguins at Cape Crozier. It was that winter trek that Cherry-Garrard dubbed The Worst Journey in the World, the title of his 1922 memoir. In his journal, Scott wrote that the Cape Crozier Expedition was “one of the most gallant stories in Po-lar History”, celebrating the explorers’ determination, but Cherry-Garrard’s The Worst Journey in the World bitterly emphasizes the futility of the search for the Emperor Penguins’ eggs. Travelling conditions were so awful that that remote place at the end of the world was perceived in terms of absence of language. According to Cherry, that journey “beggared our language: no words could express its horror”. In my paper, I analyse one of the most powerful (though neglected by academic studies) quest narrative of Polar explorations: conceived in the Heroic Age and moulded by imperial ideology, but published after the end of the First World War, Cherry’s journal deconstructs British heroism and focuses on the inner perception of the extreme Southern landscape. In his representation of Polar scenery, the author traces a story of suffering, stoicism and alienation, as well as a chronicle of the exploration of the unknown, inside and outside himself. Mapping the Antarctic blankness, Cherry quotes from many literary texts, trying to fill the void with words. As a modernist text, The Worst Journey in the World turns the description of concrete details in-to symbolic meanings; the sense of loss is embedded and recreated in an Antarctic “Waste Land”, a nightmarish underworld where language itself falls apart.